PEMBERDAYAAN MASJID DALAM IMPLEMENTASI PENINGKATAN AKHLAK REMAJA DI ERA MILENIAL - Dewi Surani; Oman Sahroni; Desi Yuliasari; Kurniawati Kurniawati (Batara Wisnu : Indonesian Journal of Community Services, 2021)
One of the community service programs in the Religious Sector 1442 H Universitas Bina Bangsa Academic Year 2021/2022 is the empowerment of mosques. The implementation of the community service program in the Religious Sector 1442 H aims to empower and improve the function of the mosque in Telaga Luhur Village. So that the program can make the people of Telaga Luhur Village an advanced society, one of which has the spirit of prospering the mosque. In comparison, the methods of implementing community service programs include community education, motivation, and competition and practice. The results of this community service activity are 1) creating awareness of the younger generation for the welfare of the mosque, 2) increase children's enthusiasm to participate in TPA, and 3) increase the enthusiasm of citizens to study Islam and pray together at the mosque. Thus, the service program by the Bina Bangsa University Service Team to the community of Telaga Luhur Village in the Religious Sector 1442 H Year 2021 in empowering mosques in Telaga Luhur Village has been carried out well.